TEKNIK LEITMOTIF SCORING SEBAGAI PENANDA PERUBAHAN SUASANA DALAM FILM THOR LOVE AND THUNDER (2022) - Ramdhan, Gracia Nuzula; Zamroni, Muhammad; Rozi, Romdhi Fatkhur (ROLLING, 2024)
Film is an audio-visual product that cannot be separated from the audio and visual elements themselves. Audio in films is something important, because audio or sound in films can provide an experience that is captured by the human listener's senses in addition to the visualization of the film. The beauty of films is captured by the visual senses, while the beauty of music is captured by the auditory senses. Apart from being an illustration of a scene, music in films can also manipulate the audience's emotions without realizing it. The interaction between visual and auditory experiences has its own charm in every setting. Thor Love and Thunder (2022) film marks changes in atmosphere in the film by using leitmotif techniques in the music or score. Leitmotif is a technique of bringing together meaning, memory, and emotion in music that can produce a richer listening experience and a better understanding of the enduring appeal of dramatic music (Stull, 2015:2). Leitmotif is a term that describes music as a marker of the presence of an idea, concept, character or motif in a story.